A Brownian agent approach for modeling and simulating the population dynamics of the schistosomiasis - Cagnin, R. L. [UNESP]; Guilherme, I. R. [UNESP]; Gonçalves, F. M.F. [UNESP]; Queiroz, J. F.P. [UNESP]; Baldassin, A. [UNESP] (My University, 2014)
Multi-agent simulations have been successfully employed in the studies of population behavior. In this work we present a Brownian agent approach for simulating and modeling the Schistosomiasis infection. Early results suggest that the proposed model describes relevant aspects of the infection conditions.
Keywords: Brownian agents; Population dynamics; Schistosomiasis; Simulation